Identification of DNA Barcodes from rbcL Chloroplast DNA in Katokkon Chili (Capsicum annuum var. chinense) Origin of Tana Toraja, South Sulawesi - Cut Muthiadin; Arma Arma; Isna Rasdianah Aziz; Masriany Masriany; Hajrah Hajrah (Journal of Multidisciplinary Applied Natural Science, 2024)
Katokkon chili (Capsicum annuum var. chinense) is a type of chili which are commonly found in Tana Toraja. It has a distinctive aroma, high spiciness, and a potential economic value but has not been widely identified and explored, thus, it is necessary to carry out molecular identification using DNA barcodes from chloroplast DNA. The aim of this study was to determine genetic variation and the results of constructing a phylogenetic tree from DNA sequences katokkon chili (C. annuum var. chinense) using the rbcL marker. This study used 6 samples of katokkon chilies (C. annuum var. chinense) and 3 outgroup samples (C. frutescens, C. chinense and C. baccatum). The stages of the research included total DNA isolation, qualitative and quantitative tests, PCR amplification using rbcL primers, and sequencing. Data analysis used is sequence alignment, phylogenetic, genetic distance matrix, haplotypes and phylogeography. The results showed genetic variation with 7 polymorphisms consisting of 4 singleton sites at the nucleotide base sequences of 6th, 525, 715 and 737, and 3 parsimony informative sites at the nucleotide base sequences 370, 616 and 902 and the haplotype distribution is divided into 4 haplotypes namely Hap_1 (A1, A2, A3, B1, B2 and B3), Hap_2 (C1), Hap_3 (C2), and Hap_3 (C3). The phylogenetic tree construction formed two clades, namely clade I consist of six samples of katokkon chilies (C. annuum var. chinense) and clade II consisting of three outgroup samples. Mark the highest bootstrap is 96 and the lowest bootstrap value is 29. Genetic distance matrix values are in the range of 0.000–0.005.